2020
DOI: 10.18388/abp.2020_5204
|View full text |Cite
|
Sign up to set email alerts
|

A proinflammatory marker in chronic rhinosinusitis: serum calprotectin

Abstract: Introduction: Studies have shown that calprotectin has a strong pro-inflammatory effect. Elevated calprotectin levels in the serum can be used as a strong clinical marker indicating the presence of inflammation. Objective: To investigate serum calprotectin levels in patients with chronic rhinosinusitis (CRS) and to determine the applicability of calprotectin as a potential molecular pro-inflammatory biomarker for CRS. Methods: The study consisted of three groups: chronic rhinosinusitis with polyps (CRSwNP grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…In this study, as the number of Cal+ cells increased, the olfactory function decreased, but the Lund‐Mackay CT and JESREC scores, reflecting CRS severity, increased. These results are similar to recent reports identifying a correlation between serum calprotectin and symptom severity in patients with CRS 12 . In addition, the tissue and blood eosinophil levels positively correlated with Cal+ cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, as the number of Cal+ cells increased, the olfactory function decreased, but the Lund‐Mackay CT and JESREC scores, reflecting CRS severity, increased. These results are similar to recent reports identifying a correlation between serum calprotectin and symptom severity in patients with CRS 12 . In addition, the tissue and blood eosinophil levels positively correlated with Cal+ cells.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to recent reports identifying a correlation between serum calprotectin and symptom severity in patients with CRS. 12 In addition, the tissue and blood eosinophil levels positively correlated with Cal+ cells. These results suggest that since calprotectin is expressed not only in neutrophils but also in eosinophils, the fact that the expression of calprotectin in tissues is correlated with the clinical findings of patients with CRS may include the previous results that increased tissue eosinophils reflect the CRS severity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Candar et al studied 26 patients with CRSwNP and found that serum calprotectin was elevated in those with aspirin-exacerbated respiratory disease (AERD) compared to those without AERD. 24 Study quality was limited by a small sample size of six AERD patients.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, due to its ability to re ect in ammation and tissue damage, circulating CLP (cCLP) has garnered signi cant attention and has also emerged as a potential biomarker in several clinical conditions[8, [14][15][16][17]. Studies have suggested its utility as a biomarker of disease activity in autoimmune rheumatic diseases, cystic brosis, chronic asthma, and different phenotypes of chronic rhinosinusitis with nasal polyps (CRSwNP) [18][19][20][21]. To note, CRSwNP frequently presents with olfactory dysfunctions, which appear to be closely correlated with the local in ammatory environment and clinical-cytological grading [22].…”
Section: Introductionmentioning
confidence: 99%